Creutzfeldt-Jakob and Vascular Brain Diseases: Their Overlap and Relationships - Balash, Yacov; Korczyn, Amos D.; Khmelev, Nadejda; Eilam, Anda; Adi, Meital; Gilad, Ronit (Frontiers in Neurology, 2021)
Only a few case reports of stroke-like onset of Creutzfeldt-Jakob’s disease (CJD) have previously been published. We aimed to analyze the neurological, imaging, electroencephalographic (EEG) and laboratory features of patients with this very rare phenomenon. Here we review the clinical characteristics, onset features and clinical course variants of stroke-like CJD in 23 such patients. The median age of the patients was 71 years (range 56–84 years); 12 were women. In 20 patients CJD was sporadic. Thirteen patients developed apoplexy-like onset of symptoms, whereas the others had prodromal non-specific complaints. Most often the patients manifested with pyramidal weakness (n=13), ataxia (n=9) and aphasia (n=8). On MRI DWI sequence, all subjects had abnormal hyperintensities in various parts of the cerebral cortex, striatum, or thalamus, while the EEG detected periodic triphasic waves only in 11. CSF 14-3-3 protein and total τ-protein were abnormal in 17 of 23 cases. All patients died, median lifespan being 3 months (range: 19 days–14 months). In conclusion, a complex of clinical, radiological, and laboratory manifestations of stroke-like onset of CJD is outlined. The clinical relationships between CJD and stroke are considered, in an attempt to highlight this rare presentation of an uncommon disease.